2020
DOI: 10.1016/j.jclepro.2020.120397
|View full text |Cite
|
Sign up to set email alerts
|

A deeper investigation of different types of core users and their contributions for sustainable innovation in a company-hosted online co-creation community

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
9
0
2
Order By: Relevance
“…In the reviewed literature (Table 1) in the domain of green innovation, it is found that majority of researchers have indicated green product, green process and green service as main element of green innovation (Tang et al, 2018; Wang, Li, et al, 2020; Zhang, Zhao, et al, 2020) which is directly related to the operational activities of the organisation. Moreover, the other angle in the green innovation literature is support activities such as culture (Wang, Xue, et al, 2020; Yang et al, 2017), Institutional quality (Sun et al, 2019) Ambidextrous green innovation, Green Learning orientation and Green Knowledge acquisition (Wang, Xue, et al, 2020), Green Mindfulness (Shah et al, 2020), Green Self‐Efficacy (Zhang, Sun, et al, 2020) and governance such as green transformational leadership (Chen et al, 2014; Çop et al, 2021; Shah et al, 2020; Singh et al, 2020).…”
Section: Prior Literature and Framework Developmentmentioning
confidence: 99%
“…In the reviewed literature (Table 1) in the domain of green innovation, it is found that majority of researchers have indicated green product, green process and green service as main element of green innovation (Tang et al, 2018; Wang, Li, et al, 2020; Zhang, Zhao, et al, 2020) which is directly related to the operational activities of the organisation. Moreover, the other angle in the green innovation literature is support activities such as culture (Wang, Xue, et al, 2020; Yang et al, 2017), Institutional quality (Sun et al, 2019) Ambidextrous green innovation, Green Learning orientation and Green Knowledge acquisition (Wang, Xue, et al, 2020), Green Mindfulness (Shah et al, 2020), Green Self‐Efficacy (Zhang, Sun, et al, 2020) and governance such as green transformational leadership (Chen et al, 2014; Çop et al, 2021; Shah et al, 2020; Singh et al, 2020).…”
Section: Prior Literature and Framework Developmentmentioning
confidence: 99%
“…Success relies on managing the ‘interacted actor’ (Ramaswamy and Ozcan, 2020) as the critical stakeholder (Loureiro et al, 2020). Reviews of users as innovators (Bogers et al, 2010) call for research on the definition of users, and more recently their roles and motivations (Roberts et al, 2014; Wang et al, 2020). Now there is a need to understand how to manage the change process involving co‐creation, and how to move to an open innovation model (Zynga et al, 2018).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Extending participation in innovation activities beyond the boundaries of the firm to include customers (Gemser and Perks, 2015), regular, core and lead users (Bogers et al, 2010; Busser and Shulga, 2018; Wang et al, 2020), and suppliers are commonplace in Business‐to‐Business (B2B) markets (Eggert et al, 2018). However, studies say little about changing long‐standing closed innovation processes to accommodate co‐creation (Zynga et al, 2018) and the functioning of customer interaction in such a process (Nardi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other types of innovation recognized in the scientific literature are plentiful. Specifically, consider radical innovations (CZAKON et al, 2020), disruptive innovations (MAHTO; BELOUSOVA; AHLUWALIA, 2020), social innovations (CAJAIBA-SANTANA, 2014), sustainable innovations (BOONS; LÜDEKE-FREUND, 2013), technological innovations (TEECE, 1986, SU;HELIAN;WANG, 2014), ecoinnovations (MALDONADO-GUZMÁN; GARZA-REYES, 2020), knowledge innovations (CHIU; LIN, 2019), innovations in business models (SHAKEEL et al, 2020;GULDMANN;HUULGAARD, 2020), management innovations (YANG et al, 2020), health innovation (PROKSCH et al, 2019), innovation capabilities (QI et al, 2020), green innovation (ZHANG et al, 2020), service innovation (FENG; MA, 2020), open innovation (LECKEL; VEILLEUX; DANA, 2020), incremental innovation (RAMPINO, 2011), and others. Clearly, innovation is a construct that is useful for different perspectives of many subject areas.…”
Section: Innovation Backgroundmentioning
confidence: 99%